EVALUATING THE ASSOCIATION BETWEEN AGE AND FREQUENCY OF COMMON FINDINGS OF ENDOMETRIAL BIOPSIES - ZULFIQAR , F; RAHAT , N; SHAHZAD , H; MOMIN , Z; JALBANI , A; BASHIR , P (Biological and Clinical Sciences Research Journal, 2023)
The current analyses aimed to assess the association between age and frequency with the common findings of endometrial biopsies. The retrospective study was conducted in the Department of Pathology, Basic Medical Sciences Institute, Karachi, from January 2014 to January 2020 to evaluate the association of age with normal endometrial phases, hyperplasia, and endometrial carcinoma in the local population. The study was conducted on a total of 103 diagnosed cases. All participants underwent immunohistochemistry testing. The Endometrial malignancies were most common in women aged 61 to 70, with an average age of 54. Hyperplasia without atypia was most common in the age group of 31 to 40 years, with an average age of 33 years, while hyperplasia with atypia was common in women aged between 41 to 50 years. The secretory and proliferative phases were most common in the 4th and third decades of life, with an average age of 42 and 39, respectively. They concluded that endometrioid adenocarcinoma is the most prevalent endometrial malignancy with the highest risk during the 6th decade, while endometrial hyperplasia without atypia is the most prevalent type of hyperplasia with the highest risk during 4th decade of life.